2021
DOI: 10.1093/g3journal/jkab440
|View full text |Cite
|
Sign up to set email alerts
|

Environment-specific genomic prediction ability in maize using environmental covariates depends on environmental similarity to training data

Abstract: Technology advances have made possible the collection of a wealth of genomic, environmental, and phenotypic data for use in plant breeding. Incorporation of environmental data into environment-specific genomic prediction (GP) is hindered in part because of inherently high data dimensionality. Computationally efficient approaches to combining genomic and environmental information may facilitate extension of GP models to new environments and germplasm, and better understanding of genotype-by-environment (G × E) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 43 publications
1
39
1
Order By: Relevance
“…Directly accounting for G × E is promising for genomic predictions in cotton, although the biggest challenge is accumulating the amount of data necessary to accurately capture these high-level interactions (thousands of markers by many environments, plus the shared effect of a marker across environments). Rogers and Holland (2022) [ 30 ] found that such high-complexity models improve the prediction accuracy only when environments overlap between the training and testing set, further demonstrating our inability to capture genotype × environments based on the measurable environmental variables.…”
Section: Resultsmentioning
confidence: 99%
“…Directly accounting for G × E is promising for genomic predictions in cotton, although the biggest challenge is accumulating the amount of data necessary to accurately capture these high-level interactions (thousands of markers by many environments, plus the shared effect of a marker across environments). Rogers and Holland (2022) [ 30 ] found that such high-complexity models improve the prediction accuracy only when environments overlap between the training and testing set, further demonstrating our inability to capture genotype × environments based on the measurable environmental variables.…”
Section: Resultsmentioning
confidence: 99%
“…In this sense, a good envirotyping protocol must be designed and conducted in order to avoid misspecification of those similarities, while differentiating the effect of different time-scales (e.g., time-windows during crop lifetime, phenology) according to the crop phenology. For example, there is no meaning in using monthly temperature values to model the growing conditions faced by an annual crop such as maize, due to the fact that during 30-day intervals, the crop goes through a wide number of development stages, and for each one of them, the crop will not face the same environment due to the differential needs and sensibility to inputs and stress factors, as evidenced by Rogers and Holland (2022). On the other hand, the use of high-resolution data, such as an hour-scale, may not aggregate value and moreover, may even be a source of noise that will limit the accuracy of the reaction-norm models (Jarquin et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…2021; Rogers et al . 2021; Rogers and Holland 2021), machine learning (Westhues et al . 2021), physiological crop growth models (Technow et al .…”
Section: Introductionmentioning
confidence: 99%
“…Within agriculture, diverse methods have been applied to the task of predicting phenotype ranging from classical statistics (Jarquin et al 2021;Rogers and Holland 2021), machine learning (Westhues et al 2021), physiological crop growth models (Technow et al 2015), to combinations of these and other methods (Messina et al 2018;Shahhosseini et al 2021). Each model contains limitations such as lacking the capacity to model complex non-linear responses (linear models) or interactions between factors, interpretability within a biological framework (machine learning models), or dependence on costly, low throughput data for calibration (crop growth models).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation